Prostate Fiducial Marker Placement in Patients on Anticoagulation: Feasibility Prior to Prostate SBRT - Iocolano, Michelle; Blacksburg, Seth; Carpenter, Todd; Repka, Michael; Carbone, Susan; Demircioglu, Gizem; Miccio, Maryann; Katz, Aaron; Haas, Jonathan (Frontiers in Oncology, 2020)
Background and Purpose: Fiducial marker placement is required in patients undergoing robotic-based Stereotactic Body Radiotherapy (SBRT) or image-guided radiation therapy (IGRT) for prostate cancer. Many patients take antiplatelet or anticoagulant medication due to other medical comorbidities. They are often required to temporarily discontinue these medications prior to invasive medical procedures as they are prone to bleed. Some patients are unable to discontinue therapy due to an elevated risk of thromboembolic events. The purpose of this study is to report this institution’s experience placing fiducial markers in prostate cancer patients who are on chronic antiplatelet or anticoagulant medication. Materials and Methods: From August 2015-March 2019 57 patients on chronic antiplatelet or anticoagulation therapy who were not cleared to stop these medications underwent transrectal ultrasound guided (TRUS) fiducial marker placement for SBRT/IGRT. All patients were monitored by a registered nurse during the procedure for prolonged bleeding that required staff to hold pressure to the area with a 4x4 gauze until it resolved. All patients were also called the following day to assess for ongoing bleeding events. Treatment planning CT scan confirmed the ideal geometry of the marker placement. Results: All 57 patients on antiplatelet or anticoagulant medication who underwent fiducial marker placement were discharged home the same day of the procedure. Four patients experienced persistent bleeding that required a nurse to hold prolonged pressure to the area. No patient experienced significant bleeding the following day or any untoward cardiovascular event. Conclusions: This series suggests the use of antiplatelet or anticoagulant medication is not an absolute contraindication to fiducial marker placement in patients undergoing SBRT or IGRT for prostate cancer. These patients should be closely monitored after the procedure for bleeding complications. Practitioners may consider the patient’s medical comorbidities, risk factors for thromboembolism and overall functional status as there is no standardized protocol for discontinuing anticoagulant or antiplatelet therapy for fiducial marker placement.